2015
DOI: 10.1128/jvi.01526-15
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Influenza Virus-Like Particle Vaccination with a Structurally Optimized RIG-I Agonist as Adjuvant

Abstract: The molecular interaction between viral RNA and the cytosolic sensor RIG-I represents the initial trigger in the development of an effective immune response against infection with RNA viruses, resulting in innate immune activation and subsequent induction of adaptive responses. In the present study, the adjuvant properties of a sequence-optimized 5=-triphosphate-containing RNA (5=pppRNA) RIG-I agonist (termed M8) were examined in combination with influenza virus-like particles (VLP) (M8-VLP) expressing H5N1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 54 publications
2
63
0
Order By: Relevance
“…A recently characterized sequence-optimized immunostimulatory RNA (termed M8) that maintains specificity for RIG-I engagement was identified as a potent antiviral agent that blocked influenza, chikungunya and dengue infection in vitro and in vivo in animal models of viral pathogenesis [14, 15]. At picomolar concentrations, M8 stimulated in MoDCs greater IFN and inflammatory responses compared to other RLR binding sequences; this immune modulation required RIG-I, but was not affected by knockdown of other RNA receptors, a clear indication of M8 selectivity for RIG-I.…”
Section: Cytosolic Nucleic Acid Sensing Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…A recently characterized sequence-optimized immunostimulatory RNA (termed M8) that maintains specificity for RIG-I engagement was identified as a potent antiviral agent that blocked influenza, chikungunya and dengue infection in vitro and in vivo in animal models of viral pathogenesis [14, 15]. At picomolar concentrations, M8 stimulated in MoDCs greater IFN and inflammatory responses compared to other RLR binding sequences; this immune modulation required RIG-I, but was not affected by knockdown of other RNA receptors, a clear indication of M8 selectivity for RIG-I.…”
Section: Cytosolic Nucleic Acid Sensing Pathwaysmentioning
confidence: 99%
“…In combination with VLP, M8 increased the antibody response to VLP immunization, provided VLP antigen sparing, and protected mice from a lethal challenge with influenza H5N1. M8-VLP immunization also led to long term protective responses against influenza infection in mice [14, 15]. Collectively, these data argue that stimulation of the conserved RIG-I pathway may be an additional target for antiviral and vaccine development.…”
Section: Cytosolic Nucleic Acid Sensing Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed STING activation by membrane disturbance caused by the entry of viral vectors, VLPs and liposomes [63]. The use of 5′-triphosphate–containing RNA, a RIG-I agonist, combined with an influenza-derived VLP was capable of increasing antibody titers and protecting mice against a lethal challenge with H5N1 [64]. Another study suggested an involvement of endogenous retrovirus-derived nucleic acids that would activate RIG-I and cGAS [65] upon VLP recognition by B cells.…”
Section: Immunology Of Npsmentioning
confidence: 99%